THE EFFECT OF OPERATIONAL EFFICIENCY, CREDIT RISK, LIQUIDITY RISK ON PROFITABILITY IN CONVENTIONAL BANKING LISTED ON THE INDONESIA STOCK EXCHANGE PERIOD 2020 – 2021 - Shikit Indra Pangesti; Shadrina Hazmi (ADISAM Publisher, 2023)
The purpose of this study was to analyze the effect of Operational Efficiency (BOPO), Credit Risk (NPL), and Liquidity Risk (LDR) on Profitability (ROA) in the banking sector listed on the Indonesia Stock Exchange for the period 2020 – 2022. This type of research is quantitative. The analysis tool used is Multiple Linear Regression. The population of this study was 31 conventional banks listed on the Indonesia Stock Exchange for the period 2020 – 2022. The sampling technique in this study used purposive sampling. The results show that Credit Risk (NPL) has no significant effect on Profitability (ROA), while Operational Efficiency (BOPO) and Liquidity Risk (LDR) have a positive effect on Profitability (ROA). Simultaneously Operational Efficiency (BOPO), Credit Risk (NPL), and Liquidity Risk (LDR) affect Profitability (ROA).